Pediculosis knowledge among schoolchildren parents and its relation with head lice prevalence - SOUZA,ARIELA B. DE (2022)
Abstract Pediculosis mainly affects school-age children worldwide. The aim of this study was to identify and analyze the knowledge of the parents and guardians of children in elementary schools in Niterói, Brazil, regarding pediculosis. Questionnaires were applied to 237 guardians of children at five 1-5 grade municipal schools. The responses were analyzed and correlated with positivity to louse infestation, detected by scalp aspiration. 73.8% of the respondents reported that their child had already been infested with lice. 32.9% presented correct responses about transmission. Incorrect responses were attributed to the air/wind, blood type and the fact that lice jump and fly. 40.1% of the respondents erroneously correlated control over the parasitosis with hygiene. A majority of the participants (58.6%) responded that pediculosis is harmful to health, while a small proportion (20.7%) considered it to be a disease. The prevalence of pediculosis was 19.8% among schoolchildren. Female sex, pruritus on the head and indifference regarding infestation were shown to be risk factors for pediculosis. The lack of perception of pediculosis as a disease may lead to naturalization of this parasitosis. Incorrect responses may add difficulty to implementation of preventive and curative approaches, which highlights the importance of dissemination of correct information about pediculosis.